Penyuluhan Kewirausahaan pada Kelompok PKK dalam Mendorong Pelaku UMK Desa Rambu-Rambu: - Rola Pola Anto; La Ode Sahili; Sitti Rahmatyah; Risman Togala (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Rambu-Rambu Village is one of the villages in Laeya District, South Konawe Regency. Rambu-Rambu Village has potential human resources, potential for agricultural and plantation products that can support entrepreneurial development. The problem faced by the community, especially the Family Welfare Empowerment Group (FWE)) is that they do not yet have the knowledge and understanding of entrepreneurship because they have never received entrepreneurship counseling from the government and universities. To overcome this problem, it is important to conduct counseling through the Institute for Research and Community Service (IRCS). The purpose of entrepreneurship counseling is to convey information to the FWE group so that they have knowledge, understanding and increase the participants' insight on how to do entrepreneurship. The method of implementing the extension is through the stages of observation and site survey, coordinating with the village government, preparing the location for the extension event, and providing tools or facilities and infrastructure, then carrying out counseling through lectures and questions and answers. Entrepreneurship counseling was held at the Rambu-Rambu Village Hall with a total of 42 participants. The results of the extension activities showed that the extension materials delivered by the extension team were very useful for the FWE group because it could provide motivation, could increase knowledge and understanding of entrepreneurship and could encourage the FWE group to be more creative and innovative in taking micro and small business opportunities. From the results of the question and answer, it was also revealed that after completing the entrepreneurship counseling activities, it is better to continue the beginner entrepreneur training activities for the practice of making micro and small business products.